Effects of short sprint interval training frequency on physical and physiological performance adaptations in male soccer players - Liu, Q.; Wang, W.; Shu, C. (Journal of Sports Science & Medicine, 2024)
The study aimed to evaluate the effects of varying frequencies (1 vs. 2 vs. 3) of short sprint interval training (sSIT) on young male soccer players' physical performance and physiological parameters. Forty young male soccer players were randomly assigned to four experimental groups engaging in 36 trials sSIT for a duration of 6 weeks as follows: once weekly (1sSIT = 4 sets of 9 × 5 sec all-out runs), twice weekly (2sSIT = 2 sets of 9 × 5 sec all-out runs), and three times weekly (3sSIT = 2 sets of 6 × 5 sec all-out runs), or an active control group which continued their soccer practice routines. Before and after the 6-week training period, physical performance (countermovement vertical jump, 20-m sprint, Illinois change of direction, Yo-Yo intermittent recovery level 1 [Yo-Yo IR 1] and kicking distance) and physiological parameters (cardiorespiratory fitness, peak and average power output) were evaluated. All sSIT groups demonstrated significant (p < 0.01) and small to very large training effects (i.e., effect size) on measured parameters. More importantly, a comparison of inter-individual variability in the adaptive changes revealed that the 3sSIT group results in lower residuals in changes in cardiorespiratory fitness and anaerobic power, coupled with lower coefficient of variations in the mean group changes and perceived exertion throughout the training period. The findings indicate that incorporating one, two, or three weekly sessions of sSIT into routine soccer training can lead to similar enhancements in soccer players' physiological and performance adaptations. More importantly, higher training frequencies result in more homogenized adaptations among team members by reducing inter-individual variability in the magnitude of the adaptive responses.